Fuzzy Logic based Smart Irrigation System using Internet of Things. (10th April 2020) - Krishnan, R. Santhana; Julie, E. Golden; Robinson, Y. Harold; Raja, S.; Kumar, Raghvendra; Thong, Pham Huy; Son, Le Hoang
Abstract: Traditional agricultural systems require huge amount of power for field watering. This paper proposes a smart irrigation system that helps farmers water their agricultural fields using Global System for Mobile Communication (GSM). This system provides acknowledgement messages about the job's statuses such as humidity level of soil, temperature of surrounding environment, and status of motor regarding main power supply or solar power. Fuzzy logic controller is used to compute input parameters (e.g. soil moisture, temperature and humidity) and to produce outputs of motor status. In addition, the system also switches off the motor to save the power when there is an availability of rain and also prevents the crop using panels from unconditional rain. The comparison is made between the proposed system, drip irrigation and manual flooding. The comparison results prove that water and power conservation are obtained through the proposed smart irrigation system. Graphical abstract: Image 1082